Questions & Answers

Question

Answers

Answer

Verified

146.1k+ views

Hint: Here we have to multiply both the equations by dividendo and componendo.

As per this rule, if $\dfrac{a}{b} = \dfrac{c}{d}$,

Then this can be expressed as $\dfrac{{a + b}}{{a - b}} = \dfrac{{c + d}}{{c - d}}$

Complete step-by-step answer:

Given, $\dfrac{a}{b} = \dfrac{c}{d}$ equation (1)

Multiplying both the equation (1) and (2)

$\dfrac{{ae}}{{bf}} = \dfrac{{cg}}{{dh}}$

By dividendo and componendo

$\dfrac{{ae + bf}}{{ae - bf}} = \dfrac{{cg + dh}}{{cg - dh}}$

NOTE:

Whenever you come to this type of problem first convert the given form to a rational form that multiplies both the equation and after applying the dividendo and componendo get the final answer.

As per this rule, if $\dfrac{a}{b} = \dfrac{c}{d}$,

Then this can be expressed as $\dfrac{{a + b}}{{a - b}} = \dfrac{{c + d}}{{c - d}}$

Complete step-by-step answer:

Given, $\dfrac{a}{b} = \dfrac{c}{d}$ equation (1)

$\dfrac{e}{f} = \dfrac{g}{h}$ equation (2)

Multiplying both the equation (1) and (2)

$\dfrac{{ae}}{{bf}} = \dfrac{{cg}}{{dh}}$

By dividendo and componendo

$\dfrac{{ae + bf}}{{ae - bf}} = \dfrac{{cg + dh}}{{cg - dh}}$

NOTE:

Whenever you come to this type of problem first convert the given form to a rational form that multiplies both the equation and after applying the dividendo and componendo get the final answer.